PSYCHOLOGICAL AND PEDAGOGICAL BASIS OF PROFESSIONAL TRAINING OF FUTURE FINE ARTS TEACHERS (American Journal of Pedagogical and Educational Research, 2023)
In the article, the psychological-pedagogical foundations of professional training of future visual arts teachers are highlighted, the methods of implementing integrative relations between them based on the use of active teaching methods are considered.